The Qur'an and the Mapanre Teme Aqorang Tradition of the Bugis Ethnicity in East Kalimantan - Mursalim, Mursalim (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
Reading the Qur'an is not only a ritual worship practice for the Bugis society, but the reading of the Qur'an is also linked to local rituals that have symbolic meanings and dimensions of very deep values amidst the plurality of Bugis society. The recitation of the Qur'an upon completion of Qur'anic studies is associated with a tradition known as 'mappanre temme aqorang'. This article aims to reveal the meaning of the ritual values of the Qur'an recitation tradition 'mappanre temme' as a local tradition of the Bugis community in the overseas country of Kalimantan. This tradition encompasses a belief system with forms and practices that can be traced to the present day. This phenomenological research uses a descriptive-qualitative approach and field-based data collection techniques by conducting in-depth interviews with the bearers of this tradition, namely the Bugis community in East Kalimantan and the religious leaders involved in the procession of this tradition. It was found that the traditional ritual of mappanre temme aqorang for the Bugis community is not just an ordinary ritual, but serves as a means of maintaining the identity of the Bugis community in the overseas country in the midst of a multicultural society in the Etam continent of East Kalimantan, both as a community that is highly religious and as a community that is loyal to ancestral traditions. In addition, the ritual serves as a glue for the Bugis' philosophical values of sipakatau, sipakalebbi and siamase-masei in social relations. Writings on Qur'anic studies and local wisdom in multicultural Indonesia have yet to be contextually and comprehensively explored as a cultural phenomenon. الملخص قراءة القرآن لمجتمع بوغيس ليست مجرد ممارسة عبادة طقسية ولكن قراءة القرآن مرتبطة أيضا بالطقوس المحلية التي لها معاني رمزية و قيم عميقة في تعددية مجتمع بوغيس. من أحد تقاليد قراءة القرآن هو تقليدختم القرآن “mappanre temme” بعد أن يكمل تعلم قراءة القرآن 30 جزءا. تهدف هذه المقالة إلى كشف معاني قيم الطقوس في تقليد قراءة القرآن المسمئ بـ